Influence of Surface and Subsidence Thermal Inversion on Pm2.5 and Black Carbon Concentration - Sanchez-Munoz, G; Rubio-Campos, M; Gramsch-Labra, E (Elsevier Ltd, 2014)
A study of particulate matter and temperature in the atmosphere in several places in Chile has been carried out in three different years with the objective of determining a common pattern of the influence of thermal inversions on PM2.5 and black carbon. Temperature measurements were used to separate days with and without inversions. In all sites it was found that the days with thermal inversions had higher black carbon or PM2.5 than days without inversions. In the rural site, black carbon was 57% higher during inversion days. In the downtown Santiago site the PM2.5 was 35% higher during inversion days. At the western Santiago site it was possible to separate the days into three categories; only surface, surface and subsidence, and no thermal inversion. In days with both types of inversion, PM2.5 was 84% higher than days without any type of inversion. During days with only surface inversion, PM2.5 was higher only during the morning and the average PM2.5 was only 14% higher. Although during inversion days the concentrations were higher, it was not possible to find a significant correlation between the strength or intensity of the inversion with black carbon or PM2.5 in the sites without temperature measurements as function of height. However, when this data is available, a moderate correlation is found, indicating that the complete vertical temperature profile is needed in order to find a relationship between those variables. © 2014.